Caracterização de superfícies seletivas de frequência de periódicas e não-periódicas - Araújo, Lincoln Machado de (2014)
The past years have seen a great interest in the use of frequency selective surfaces (FSS), as spatial filters, in many microwave applications. Among these, we highlight applications in telecommunication systems (such as satellite communications and radar), high gain antennas (combined with planar antennas) and (home and industrial) microwave ovens. The FSS is usually composed of two-dimensional periodic arrays, with equally spaced elements, which may be metallic patches (printed on dielectric substrates) or aperture (holes in thin metal surfaces). Using periodic arrays, the FSS have been able to meet the demands of the telecommunications industry. However, new demands are finding technological limitations. In this context, adverse filtering requirements have forced designers to use FSS optimization methods to find specific formats of FSS elements. Another alternative that has been used to increase the selectivity of the FSS is the cascaded FSS, a simple technique that has as main drawback the increased dimensions of the structure, as well as its weight. This work proposes the development of a new class of selective surfaces frequency (FSS) composed of quasi-periodic (or non-periodic) arrangements. The proposed FSS have no array periodicity, in relation with the spatial position of their elements. The frequency responses of these structures were simulated using commercial softwares that implement full-wave methods. For the purpose of validation of this study, FSS prototypes were built and measured, being possible to observe a good agreement between simulated and measured results. The main conclusions of this work are presented, as well as suggestions for future works.